(untitled) (Studia Prawnicze / The Legal Studies, 2013)
W 2006 roku UNCITRAL (United Nations Commission on International Trade Law – Komisja Międzynarodowego Prawa Handlowego Narodów Zjednoczonych) zmieniła i unowocześniła Ustawę Modelową (UNCITRAL Model Law) o międzynarodowym arbitrażu handlowym z 1985 roku. Pomimo że Ustawa Modelowa – stanowiąc alternatywę dla konwencji międzynarodowej – nie prowadzi do skutku ujednolicenia prawa (a więc stworzenia norm wspólnych, o identycznej treści dla poszczególnych państw), to stanowi ona źródło prawa, na którym w szerokim zakresie opierają się systemy prawne w różnych jurysdykcjach. Jest ona jednocześnie aktem o olbrzymim znaczeniu dla formowania nowoczesnych ustawodawstw arbitrażowych, w tym także ustawodawstwa polskiego. UNCITRAL (United Nations Commission on International Trade Law) amended and modernized the UNCITRAL Model Law on International Commercial Arbitration of 1985 in 2006. The provisions of the Polish Civil Procedures Code were aligned to the Model Law (in its original wording of 1985) on 28 July 2005, by amending Articles 1154 – 1217 accordingly, simultaneously repealing the regulations to date on the arbitration court – i.e. Articles 695 – 715 of the CPC. However, the Polish legislator has not yet fully aligned the regulations of the CPC to the amendments of the Model Law adopted in 2006. A new version of the Arbitration Rules was adopted by UNCITRAL on 29 June 2010, which was published in English on 12 July 2010 (and later in the other official UNCITRAL language versions).The amendments made to the Model Law and the Rules demonstrate the importance which UNCITRAL attaches to the alignment of the regulations it creates to the requirements of legal transactions and to the assurance of modernity and flexibility of the proposed legal structures. As a result, both of these acts of law should be considered equally precursory, which is of key importance to the international arbitral order. An analysis has been conducted in this publication of the interrelationships between arbitration and the general judiciary, together with an analysis of selected issues related to the UNCITRAL Arbitration Rules and arbitration proceedings conducted in accordance with these rules.